Identifikasi Senyawa Fitokimia Ekstrak Daun Waru (Hibiscus Tiliaceus) - Kristina Tresia Leto; Aiynun Rukmanti; Asti Junianti; Mutia malmar; Sasmita Putri Hairani (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Waru leaves (Hibiscus tiliaceus) are one of the herbal plants that grow well in Indonesia. Empirically, waru leaves have many benefits for treating flu, accelerating the maturation of boils, tonsillitis, and can be used as a hair fertilizer. This study aims to determine the content of waru leaves (Hibiscus tiliaceus). Waru leaves (Hibiscus tiliaceus) are extracted by maceration with methanol solvent. The extraction results then go through a color reaction compound test process and confirmation test. Testing of color reaction compounds includes steroids, saponins, flavonoids, alkaloids, and tannins. This study aims to analyze the chemical compound content contained in waru leaves (Hibiscus tiliaceus) extracted using methanol solvent. This research method includes maceration extraction and chemical compound screening tests using chemical reagents. The results showed that waru leaves extracted using methanol solvent contain steroids, alkaloids, tannins, and saponins. It can be concluded that the chemical compounds contained in hibiscus leaves (Hibiscus tiliaceus) are relevant to human health.